Macrozoobenthos Diversity as A Bioindicator of Water Quality in River Sesaot Village Narmada West Lombok - Ernawati Ernawati; Immy Suci Rohyani; Rifki Hidayatul Ardi; Annisa Firda Wahyuningsih; Baiq Hana Tasya Muflihah; Rizki Aditia Zubair (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sesaot River is a river located in Narmada, West Lombok. The Sesaot River has been widely used by the surrounding community for their agricultural, plantation and daily activities. The high activity of the people around the river causes a decrease in the quality of river water. Macrozoobenthos is a bioindicator that can be used to describe a water's air quality. The purpose of this research is to examine the water quality of the Sesaot River utilizing macrozoobenthos as a bioindicator. The study was carried out at three different locations along the Sesaot River: upstream, middle, and downstream. At each observation site, macrozoobenthos ecological study and measurements of river water physical and chemical parameters were performed. According to observations, the pH, DO, and TDS of river water remain within the range of acceptable environmental quality standards. The macrozoobenthos found in the Sesaot Narmada river consist of 3 classes, 8 families and 8 species. Gastropoda, Mollusca, and Insecta are the third class discovered. The macrozoobenthic diversity index values discovered ranged from 0.8 to 1.35. Based on these findings, the macrozoobenthos diversity at the three locations is low. The uniformity index values obtained at the three stations ranged from 0.03 to 0.07, indicating that the distribution of individuals was unequal and unbalanced. At the three stations, the dominance index ranged from 0.27 to 0.55. Based on the findings, it is possible to conclude that the water quality of the Sesaot Narmada river is moderately to badly polluted.